2019
DOI: 10.1186/s12864-019-6411-9
|View full text |Cite
|
Sign up to set email alerts
|

Proximal femoral head transcriptome reveals novel candidate genes related to epiphysiolysis in broiler chickens

Abstract: BackgroundThe proximal femoral head separation (FHS) or epiphysiolysis is a prevalent disorder affecting the chicken femur epiphysis, being considered a risk factor to infection which can cause bacterial chondronecrosis with osteomyelitis in broilers. To identify the genetic mechanisms involved in epiphysiolysis, differentially expressed (DE) genes in the femur of normal and FHS-affected broilers were identified using RNA-Seq technology. Femoral growth plate (GP) samples from 35-day-old commercial male broiler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 80 publications
2
19
2
Order By: Relevance
“…According to the position in the genome of the NCBI database, the lncRNAs ENSGALG00000040226, ENSGALG00000033872 and ENSGALG00000032326 are close to the genes SOX9, COL11A1 and SOX8, respectively, and may be involved in the regulation of these important genes for bone development. The SOX9 and SOX8, two transcriptions factors acting on endochondral ossification, have recently been associated to femur epiphysiolysis [15]. In the current study, it was possible to identify several DE genes involved with BCO development, even using a small number of samples per group, as can be seen in several RNA-Seq studies, when groups are well characterized [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…According to the position in the genome of the NCBI database, the lncRNAs ENSGALG00000040226, ENSGALG00000033872 and ENSGALG00000032326 are close to the genes SOX9, COL11A1 and SOX8, respectively, and may be involved in the regulation of these important genes for bone development. The SOX9 and SOX8, two transcriptions factors acting on endochondral ossification, have recently been associated to femur epiphysiolysis [15]. In the current study, it was possible to identify several DE genes involved with BCO development, even using a small number of samples per group, as can be seen in several RNA-Seq studies, when groups are well characterized [24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 81%
“…Although several studies are available evaluating femur, it is known that the lesion status differ between bones [3], and that high incidences of tibia BCO has been previously reported in broilers [20]. Nowadays, there are just few studies addressing the molecular mechanisms involved with femur BCO [13][14][15] and no information regarding tibia BCO is available which highlights the importance of our study, since it brings novel and relevant knowledge to the field. Furthermore, this condition is observed in males and females, and an influence of sire line on susceptibility for this trait has already been found [20].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Both IL-1β and TNFα act via catabolic mechanisms within bone and proinflammatory mechanisms systemically, which could be contributing to the lack of healing seen in BCO. Other studies investigating these cytokines in osteomyelitis found increased TNFα in the early stage of chronic osteomyelitis rather than the late stage [33]. Another study involving the stimulation of blood from patients with osteomyelitis with lipid polysaccharides (LPS) did not affect the expression of TNFα or other cytokines in the blood [34].…”
Section: Discussionmentioning
confidence: 98%
“…The Embrapa Swine and Poultry National Research Center Ethical Committee of Animal Use (CEUA/CNPSA) approved this study under the protocol number 012/2012. The samples used were previously collected from chickens at 35 days of age, as described in detail by Peixoto et al [27]. Briefly, 29 male broilers from a commercial line (14 normal and 15 lameness) were selected and sent to the Embrapa Swine and Poultry National Research Center, in Concórdia, SC, Brazil for sampling.…”
Section: Animals and Sample Collectionmentioning
confidence: 99%